FAMILY PERCEPTION OF NURSES' CARING BEHAVIOR AND INDEPENDENCE IN CARE FOR PULMONARY TUBERCULOSIS - M Sagala, Adi Brando; Nursasi, Astuti Yuni; Rachmawati, Utami (Alauddin Scientific Journal of Nursing, 2025)
Pulmonary Tuberculosis cases are estimated at 969,000 people and an incidence of 354 per 100,000 population in Indonesia in 2022. The estimated TB caseload is 2,386 out of 635,129 population in North Lampung District. TB control is implemented with the integration of the Healthy Indonesia Program and Public Health Care to achieve health through family independence in treating TB. This cross-sectional study aims to determine the relationship between family perceptions of nurses' caring behavior and family independence in caring for TB in the work area of the North Lampung District Health Center. A total of 90 family samples were selected through two stage cluster randomization. The instrument was a questionnaire developed based on Swanson's Caring theory and indicators of family independence according to Kepmenkes 279 of 2006. The results showed that the perception of caring behavior was good (51.1%); families were less independent (66.7%); there was a significant relationship between family perceptions of nurses' caring behavior and family independence with a value of p=0.006 (95% CI; OR; 1.579-10.773). The majority of families with good perceptions of nurses' caring behavior had a 4.1 times greater chance of becoming independent. It is hoped that the results of this study will serve as a basis for strengthening the caring behavior of nurses through TB program training and instilling the value of caring nurses from an early age.